From an Unknown Territory to a Nation’s Motherland: An Analysis of the Memoirs of the Republic’s First Generation of Intellectuals - U. Ceren Ünlü; Mehmet Ertan (Siyasal: Journal of Political Sciences)
This article aims to analyze the memories and autobiographies of six intellectuals who witnessed and contributed to the foundation of the Turkish Republic and played important roles in the cultural policies of the era of the early Republic of Turkey. In the analysis, the sociological concept of generation is utilized as a conceptual framework. Characterizing a group of people that not only share approximating birth dates and locations but also have experienced similar historical moments or political and socioeconomic transformations as a generation, this article regards Şevket Süreyya Aydemir, Süleyman Edip Balkır, İsmail Hakkı Baltacıoğlu, Yakup Kadri Karaosmanoğlu, Ahmet Emin Yalman and Hasan Âli Yücel as members of the same generation. An in-depth analysis of the memoirs and autobiographies reveals two common themes among these people’s memories: first, because they were born and grew up on the western side of the Ottoman lands, they were all strangers to Anatolia before World War I or the foundation of the Republic; and, second, all six intellectuals believed in the fact that the path of turning Anatolia into a modernized and secularized homeland passed through education. Their strangeness to Anatolia and the importance of education for its socio-cultural development were highly related because the transformation of Anatolia through education not only aimed to create a homeland but also ended the strangeness between these intellectuals and Anatolia.